Strategic challenges of newspaper publishing in an international perspective. (September 2019) - Kolo, Castulus
An analysis of newspaper industries in their national contexts exhibits strategic clusters of similar challenges, imposed by digital transformation and socio-economic change. While growth of media in general, newspaper reach, and Internet penetration are dominant factors framing the prosperity of newspaper publishing, dynamics of digital revenues from advertising and circulation still vary substantially also within such clusters. Only in very few countries, publishers achieve to collectively combine (still) growing overall revenues with advanced digital transformation.